Estimate of the future water consumption in Northern Juazeiro / EC - Costa, Luana Letícia Oliveira; Feitosa, Hernandes de Oliveira; Silva, João Alvino Sampaio da; Santos, Vagner Sales dos (Revista Hipótese, 2017)
Water is of utmost importance to man, without it is impossible for life to continue. Over the years, due to extreme use this feature has become increasingly scarce in quantity but also in quality. According exaggerated population growth also increases the use and consumption of water at an alarming rate, it is already known that this is a finite resource. This study aims to estimate the per capita consumption of Juazeiro population - EC, as well as propose solutions regarding the consumption of water and its preservation. The survey was based on information provided by the competent body of the municipality sanitation CAGECE. It was then possible to compare year 2004 data to 2014, related to water consumption and the volume of water available in 2004, respectively for 2014, to be held the projection of estimated water consumption per capita for population Juazeiro-EC for a horizon of 10 years (2015 to 2025). In the projection it was concluded that according to the increase in population, distributed volume of water also increases. The per capita consumption can not exceed the current otherwise the city will suffer from water scarcity.